(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Furthermore, the main thesis of this work will affirm that the lacanian notion of “the real” or “primordial repressed”, reformulated by Žižek, would rearrange the theoretical limits of the Habermasian communicative action and, at the same time, would allow setting up a hypothetical but still universal truth, essential for a new critique of ideology.